1987
DOI: 10.1016/0009-2509(87)80160-4
|View full text |Cite
|
Sign up to set email alerts
|

Network model for straining dominated particle entrapment in porous media

Abstract: network model has been developed to study and describe formation damage resulting from particle entrapment in porous media by straining or size exclusion. Unlike the previous network models, this model considers the simultaneous entry ofa number of particles into the network, as well as the effects of fluid flow on the particle transport path. A systematic study has been carried out on the flow and entrapment of monodispersed particles as well as particles with a size distribution through different networks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 13 publications
1
46
0
1
Order By: Relevance
“…In reality, however, both fines and pore constrictions will have respective size distributions. In such cases, Rege and Fogler [83] have shown that the higher the overlap between the size distribution of fines and that of pore constrictions, the higher is the extent of plugging and vice versa. Table 3 presents some qualitative results on whether plugging or other possible types of deposition would possibly occur as determined by the ratio of the size of fines to size of the pore constrictions [74,84].…”
Section: Size Of Colloidal Finesmentioning
confidence: 99%
“…In reality, however, both fines and pore constrictions will have respective size distributions. In such cases, Rege and Fogler [83] have shown that the higher the overlap between the size distribution of fines and that of pore constrictions, the higher is the extent of plugging and vice versa. Table 3 presents some qualitative results on whether plugging or other possible types of deposition would possibly occur as determined by the ratio of the size of fines to size of the pore constrictions [74,84].…”
Section: Size Of Colloidal Finesmentioning
confidence: 99%
“…Several 2D Fogler, 1988, 1987;Sharma and Yortsos, 1987;Lee and Koplik, 1994) and 3D (Siqueira et al, 2003) network models have been used for filtration simulation. Using a network model to study the filtration process (Rege and Fogler, 1987) has two advantages. First, particle deposition and migration are simultaneously accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this research is to investigate a simplified approach to describe filter media. There have been numerous previous studies on modeling filter media, using various approaches such as complex network models [1][2][3] and elaborate depth filtration approaches [4,5], which attempted to provide an accurate physical description of the filter media. In this study, more simplified model structures were investigated where the porous structure is represented by simple layers of parallel pores [6].…”
Section: Introductionmentioning
confidence: 99%